Perioperative Coagulation Management in Liver Transplant Recipients. Issue 4 (April 2018) - Bezinover, Dmitri; Dirkmann, Daniel; Findlay, James; Guta, Cosmin; Hartmann, Matthias; Nicolau-Raducu, Ramona; Mukhtar, Ahmed M.; Moguilevitch, Marina; Pivalizza, Evan; Rosenfeld, David; Saner, Fuat; Wray, Christopher; et al.
Abstract : Abstract: We review contemporary coagulation management for patients undergoing liver transplantation. A better understanding of the complex physiologic changes that occur in patients with end-stage liver disease has resulted in significant advances in anesthetic and coagulation management. A group of internationally recognized experts have critically evaluated current approaches for coagulopathy detection and management. Strategies for blood component and factor replacement have been evaluated and recommended therapies proposed. Pharmacologic treatment and prevention of coagulopathy, management of patients receiving antiplatelet medications, and the role of transesophageal echocardiography for early detection and management of thromboses are presented. Abstract : The authors present a thorough review of coagulation in liver transplantation with special attention to the perioperative issues.